Toxoplasmosis 2017
DOI: 10.5772/intechopen.68619
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Toxoplasmosis: In Vivo Impact of Toxoplasma gondii Infection on Myogenesis and Neurogenesis

Abstract: Congenital toxoplasmosis (TC) from Toxoplasma gondii positive mother to child transmission results in fetal death, abortion, or infantile neurologic and neurocognitive deficits as well as chorioretinitis. This study aims to analyze the morphological changes in brain and skeletal muscle cells of Swiss mouse embryos during experimental congenital toxoplasmosis. Swiss mice, before mating, were gavage inoculation infected with approximately 25 or 50 cysts of ME-49 strain T. gondii. Eighteen day postcoitus maternal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…We chose the type II strain ME49 that exhibits reduced virulence compared to the laboratory-adapted RH strain, thus avoiding the confounding factor of high levels of host cell lysis by the latter (Kirkman et al, 2001). Moreover, previous observations from our group showed that vertical transmission of T. gondii induces alterations in the fetal myogenesis (Gomes and Barbosa, 2016). Low levels of parasitism were detected when C2C12 cells were infected with ME49 tachyzoites (5% at 48 hpi and 10-30% at 144 hpi).…”
Section: Discussionmentioning
confidence: 69%
“…We chose the type II strain ME49 that exhibits reduced virulence compared to the laboratory-adapted RH strain, thus avoiding the confounding factor of high levels of host cell lysis by the latter (Kirkman et al, 2001). Moreover, previous observations from our group showed that vertical transmission of T. gondii induces alterations in the fetal myogenesis (Gomes and Barbosa, 2016). Low levels of parasitism were detected when C2C12 cells were infected with ME49 tachyzoites (5% at 48 hpi and 10-30% at 144 hpi).…”
Section: Discussionmentioning
confidence: 69%
“…To assess the relationship between congenital infection by T. gondii and the damages to embryonic development, we used a model in which pregnant females were intragastrically infected with cysts of the ME49 strain of T. gondii, aiming to experimentally emulate the ingestion of contaminated bradyzoite cysts-bearing meat by pregnant female hosts. Our laboratory have described that intragastric inoculation of Swiss Webster mice with 25 or 50 Me49 cysts led to significant malformations to the skeletal muscle and brains and T. gondii cysts were found within fetal tissues (Gomes and Barbosa, 2017). We tested different cysts concentrations (2, 5 and 10) in pregnant females on the tenth day of gestation, in order to identify the most appropriate inoculum which would provide the best chance of post-infection survival, while still displaying significant fetal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…The human TLR11 gene consists of some stop codons, and its expression in human does not perform for a full-length protein. However, our belief in TLR11 and other TLRs not expressed in human would provide us with prominent understanding of the pathogenesis of a variety of important human infections ( 2 , 3 , 13 , 14 ). Investigation of TLR11 can contribute to promote our knowledge on human immune response against bacterial and apicomplexan pathogens carrying this kind of pathogen-associated molecular patterns because TLR11 regulates immune responses that share with other TLRs.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of chronic toxoplasmosis is asymptomatic, and the most common signs in acute toxoplasmosis are mainly lymphadenopaty ( 2 ). In congenital toxoplasmosis, if a mother is exposed to T. gondii for the first time during her pregnancy period, it may cause serious damages to the fetus such as central nervous system failure, spontaneous abortion, and fetal death, and a set of symptoms such as rash, fever, liver enlargement, jaundice, hydrocephalus, microcephaly, and retinochoroiditis ( 3 ). In immunocompromised individuals (e.g.…”
Section: Introductionmentioning
confidence: 99%